Ni2+-Assisted Hydrolysis May Affect the Human Proteome; Filaggrin Degradation Ex Vivo as an Example of Possible Consequences - Podobas, Ewa Izabela; Gutowska-Owsiak, Danuta; Moretti, Sébastien; Poznański, Jarosław; Kulińczak, Mariusz; Grynberg, Marcin; Gruca, Aleksandra; Bonna, Arkadiusz; Płonka, Dawid; Frączyk, Tomasz; Ogg, Graham; Bal, Wojciech (Frontiers in Molecular Biosciences, 2022)
Deficiency in a principal epidermal barrier protein, filaggrin (FLG), is associated with multiple allergic manifestations, including atopic dermatitis and contact allergy to nickel. Toxicity caused by dermal and respiratory exposures of the general population to nickel-containing objects and particles is a deleterious side effect of modern technologies. Its molecular mechanism may include the peptide bond hydrolysis in X1-ST-cp-H-c-X2 motifs by released Ni2+ ions. The goal of the study was to analyse the distribution of such cleavable motifs in the human proteome and examine FLG vulnerability of nickel hydrolysis. We performed a general bioinformatic study followed by biochemical and biological analysis of a single case, the FLG protein. FLG model peptides, the recombinant monomer domain human keratinocytes in vitro and human epidermis ex vivo were used. We also investigated if the products of filaggrin Ni2+-hydrolysis affect the activation profile of Langerhans cells. We found X1-ST-cp-H-c-X2 motifs in 40% of human proteins, with the highest abundance in those involved in the epidermal barrier function, including FLG. We confirmed the hydrolytic vulnerability and pH-dependent Ni2+-assisted cleavage of FLG-derived peptides and FLG monomer, using in vitro cell culture and ex-vivo epidermal sheets; the hydrolysis contributed to the pronounced reduction in FLG in all of the models studied. We also postulated that Ni-hydrolysis might dysregulate important immune responses. Ni2+-assisted cleavage of barrier proteins, including FLG, may contribute to clinical disease associated with nickel exposure.